Financial Feasibility of Cocoa Farming in Andomesinggo Village Besulutu Sub-district of Konawe District - Aan Wilhan Juliatmaja; Helviani Helviani (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
This study aimed to determine the financial feasibility of cocoa farming in Andomesinggo Village Besulutu Sub-district Konawe District. Sampling method was Stratified Random Sampling. The financial analysis criteria used were Net Present Value, Net Benefit Cost Ratio, Internal Rate of Return, Pay Back Period, and Sensitivity Analysis. The results showed that cocoa farming in Andomesinggo village was financially feasible to be cultivated. Based on the result of the investment feasibility assessment at 18% DF, it was obtained that NPV was Rp 20,500,335, NBCR of 3.59%, IRR of 55.42% and PBP value of 4.54 which identified that the cocoa farming in Andomesinggo village returned the investment in the early of fifth year. Based on sensitivity analysis, the condition of cocoa farming is still feasible to be cultivated even though fertilizer price was up to 15%, cocoa price decreased to 10%, cocoa production decreased to 20%.